Teaching english as a foreign language: issues and challenges - LARABA, Ahmed (Journal of Human Sciences, 2001)
Serious and basic research has to be done on the teaching of English as a foreign language in Algeria. It should be based on the functional distribution of the four skills i.e. listening, speaking and writing. Our teaching materials should serve as tools to reinforce these skills.